Espaces et politiques de la frontière au Groenland. Les projets miniers comme voie de territorialisation de l’État ? - Bailleul, Pia (L’Espace Politique, 2024)
International audience Spaces and frontier politics in Greenland. Mining projects as a way of territorializing the state? -- Since the 1990s, Greenland has been developing its mining industry around the “frontier area”, a strategy of subsoil exploration and mapping. The aim is to achieve economic independence from Denmark, based on a nationalist definition of the resource frontier. However, between 2013 and 2021, the Kuannersuit mining project, which would initiate the switch to exploitation, generated massive social opposition. Drawing on ethnographic data relating to this conflict collected between 2016 and 2022, as well as industrial documents from the mining company, this article examines this conflict in terms of its engagement with this national frontier. In what ways does industrial intervention affect its deployment, and to what extent does the state operate its own territorialization through industrial development? The article begins by highlighting the phenomenon of spatial redefinition around a volume of resources controlled by the state - a frontier volume - generated by mining enclavement. It then analyzes territorialization through private-sector discharge. Finally, it examines the paradox of a border that is simultaneously a space of resources and state regulation, and a space of speculation and commercial appropriation. It is thus intended as a contribution to the literature on frontier zones and extractivism. Depuis les années 1990, le Groenland développe l’industrie minière autour de la « zone frontière », stratégie d’exploration et de cartographie des sous-sols. Cette orientation vise à permettre l’accession économique à l’indépendance vis-à-vis du Danemark, fondant une définition nationaliste de la frontière des ressources. Le projet minier de Kuannersuit, qui permettrait d’amorcer la bascule vers l’exploitation, génère pourtant entre 2013 et 2021 une opposition sociale massive. S’appuyant sur des données ethnographiques relatives à ce conflit récoltées entre 2016 et 2022, ainsi que sur ...